Gibt es eine Philosophie der Technik? Studien zur Wissenschaft, Technologie, Utopie und Dystopie - Sanmartín Esplugues, José (Mechane, 2020)
In this paper, after answering affirmatively the question of whether or not the philosophy of technique exists, the relationship between science, technique and technology is analyzed first. Secondly, a reflection is developing on the role played by science / technology in the search for utopia. In this context, the virtues and negative consequences of the growing digitalization process are underlined. Among the negative effects the author highlights the extension of foolishness (“necedad” in Spanish from Latin “nescio”: not knowing and not wanting to know) as an ideal life, in which the Kantian formula „Sapere aude“ (dare to know) is being replaced by „Iungere aude“ (dare to connect).